“Effect of post-kidney transplant diabetes mellitus on long-term outcomes in a cohort of pediatric kidney transplant recipients from 2005 to 2022.” Survival analysis - Lina Maria Serna-Higuita; Maria Alejandra Calvo-Herrera; Angelica Maria Serna-Campuzano; María Carolina Isaza-Lopez; Esteban Villegas-Arbeláez; Luisa Fernanda Rojas-Rosas; Carolina Lucia Ochoa-García (BMJ Paediatrics Open)
Background Post-transplantation diabetes mellitus and carbohydrate intolerance (PTDM/iCHO) are complications following solid organ transplantation, which significantly increases the risk of graft loss and mortality. However, data concerning long-term outcomes in paediatric kidney transplant recipients with PTDM/iCHO are scarce. This study aimed to evaluate the risk of graft loss in paediatric kidney transplant recipients with PTDM or iCHO compared with non-PTDM/iCHO.Methods The study cohort included patients aged <18 who underwent a kidney transplant in a transplant centre from 2005 to 2022. The primary outcome was graft survival loss; secondary outcomes were acute rejection, renal function and mortality. Cumulative incidence of graft loss and acute rejection was estimated, considering death a competing risk. Fine and Gray’s proportional subdistribution hazard model was used to analyse the effect of PTDM/iCHO status on the event.Results Seventy-six paediatric kidney transplant recipients were included. The incidence of PTDM and iCHO was 6.6% and 9.2%, respectively. Patients with PTDM/iCHO had a significantly higher cumulative graft loss incidence than those without (34.4% vs 13.9% at 36 months, p<0.008). Multivariable analysis revealed a threefold increased risk of graft loss in patients with PTDM/iCHO (HRadjusted 3.33, 95% CI 1.19 to 9.30, p=0.022). PTDM/iCHO was associated with a higher incidence of acute rejection (33.3% vs 14.5% at 1 year, p=0.025). Patients with PTDM/iCHO also exhibited significantly worse eGFR at all time points compared with patients without PTDM/iCHO (p=0.036)Conclusion Patients with PTDM and iCHO had a higher risk of graft loss and lower renal function in paediatric kidney transplant recipients. This justifies close monitoring of metabolic complications in these patients.